Environmental escalations to social inequities: Some reflections on the tumultuous state of Gaia. (January 2022) - Rodrigue, Michelle; Romi, Andrea M.
Highlights: Reflects on the environmental crises and their interlinkages with social inequities. Conceptualize accounting feedback loops at the individual level using Gaia theory. Feedback loops highlight interconnectedness of the natural and social environments. Individualized accounting aims to complement current SEA research and praxis. Individualized accounting intends to nurture power and agency in collective action. Abstract: This essay reflects on the current environmental crises and their complex interlinkages with social inequities, calling for individualized accounting to empower and facilitate a collective agency necessary to counter socio-environmental system deterioration. Drawing on Gaia theory (Lovelock, 1983, 2006 ) and its attention to an evolving system comprised of all living and non-living things, self-regulated by virtue of feedback loops, we address the notion that nature and society are interconnected in their anthropocentric climate ramifications. We discuss opportunities for accounting researchers to intensify system thinking, providing insights into and accounts of the interconnected nature of the natural and social environments. By means of feedback loops, we propose individualized system accountings, assisting individuals in recognizing and appreciating the web of repercussions resulting from their actions, and encouraging individual engagement in and accountability for our current "system crises." Our contribution is found in assembling knowledge of the reciprocal evolution of social and environmental ramifications within a complex system view, offering individualized accounting to complement current social and environmental accounting research and praxis. Adopting Latour (2017) 's views on "dis-hoping" (putting trust into action rather than mere hope), we argue the importance of recognizing that we are savior-less and that the emancipatory potential of accounting might lie in providing individual, local, and experiential knowledge of the influence on and consequences from our Gaian crisis, ultimately empowering individuals to act holistically. Altogether, we dis-hope our discussions may provide a springboard to a more encompassing, more complex, and messier approach to research, one placing socio-environmental interconnections center stage.